Makna Pendidikan Karakter Dalam Strategi Pembelajaran Di Setiap Sendi-Sendi Pendidikan - Aslan, Aslan (MADINAH, 2017)
Education is inseparable from the characters that shade it. Because it is impossible to say education without character, and perhaps to say that education is inseparable from the characters that can shape the child's behavior. In this connection, character education has lost its meaning in the context of education in nature. This is because, almost as a whole character has been submitted to the school without the cooperation of parents and society. In fact, the nature of character education is in the family environment. The family as the first and main socialization pursued by the child, so the strategy or method implanted to the child must be able to absorb good positive values ​​so that in the continuing education in school, the teacher only leads without teaching, instilling the values ​​of character in school. Therefore, the educational strategy must be in accordance with the nature, that is in line with the mission of the Prophet.